2019
DOI: 10.21203/rs.2.16307/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitude, Practice and its Associated Factors towards Diabetes Complications among Type 2 Diabetic Patients at Addis Zemen District Hospital, Northwest Ethiopia

Abstract: Background The aim of this study was to assess the level of attitude, practices, and its associated factors towards complications of diabetes mellitus among type 2 diabetes patients.Methods A cross-sectional study was conducted among Type 2 diabetes patients visiting the diabetes clinic at Adiss Zemen District Hospital in Northwest Ethiopia. Interviewer administered structured questionnaire was used to collect data from 402 patients. Multivariable logistic regression was used to determine factors associated wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
4
5
0
Order By: Relevance
“…Regarding practice, our study showed that 36.4% of the patients with T2DM had good practices with regard to their disease. In Ethiopia, less than half of patients with T2DM had good practices regarding T2DM and its complications [26]. Similarly, our ndings were consistent with those reported in Sri Lanka and Lebanon [3,36].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Regarding practice, our study showed that 36.4% of the patients with T2DM had good practices with regard to their disease. In Ethiopia, less than half of patients with T2DM had good practices regarding T2DM and its complications [26]. Similarly, our ndings were consistent with those reported in Sri Lanka and Lebanon [3,36].…”
Section: Discussionsupporting
confidence: 90%
“…Findings of this study showed that 58.7% of the patients had positive attitudes toward their disease. Our results were comparable to those reported by Belsti et al in Ethiopia in which [26]. However, in this study attitude scores were not signi cantly associated with educational level of the patients as was shown in Belsti's study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A good attitude towards DM complications improves Practice in Diabetes patients that helps them change any harmful dietary and lifestyle habits. 4 During the past 30 years, there has been notable modification in way of life of people largely resulting in diminished physical activity and unhealthy eating habits. These changes have had a significant negative impact on the health of the society and are considered to be accountable for the epidemic of noncommunicable diseases and their complications.…”
Section: Introductionmentioning
confidence: 99%